Influenza vaccine effectiveness among children, 2011 - 2021: a test-negative design-based evaluation - Li-ping YI; Wan-qing ZHANG; Li-ling CHEN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo evaluate influenza vaccine effectiveness (VE) in preventing laboratory confirmed influenza illness among children aged 6 - 59 months during 2011 - 2021, and to provide evidences for improving vaccination recommendation and policy-making. MethodsBased on a prospective influenza surveillance conducted at the Soochow University Affiliated Children's Hospital in Suzhou city, Jiangsu province from October 2011 to May 2021, we conducted a test-negative case-control study. The participants of the study were selected from 5 554 influenza-like illness (ILI) and 7 737 severe acute respiratory infection (SARI) outpatients/inpatients aged 6 - 59 months and with nasopharyngeal swab/sputum specimen test for influenza virus nucleic acid in the surveillance and influenza vaccination records of all the ILI and SARI patients were checked retrospectively. The cases of the study were influenza virus-positive ILI (n = 517) and SARI (n = 582) patients aged 6 - 59 months; the controls were 1 : 2 age- and clinic attending/hospital admission date-matched influenza virus-negative ILI/SARI patients. The adjusted odds ratio (aOR) of vaccination and VE were estimated using conditional logistic regression. ResultsThe vaccination records were available for 73.3% (9 747) of the registered patients and the observed vaccination rate was 1.79% (174/9 747). The overall VE for all the ILI/SARI patients was 36.8% (95% confidence interval [95% CI]: - 4.7% - 61.9%); the VE was 26.7% (95% CI: - 34.8% - 60.2%) for the ILI and 53.1% (95% CI: - 17.0% - 81.2%) for the SARI. The VE were 28.9% (95% CI: - 31.2% - 61.5%) and 51.2% (95% CI: - 21.3% - 80.4%) for the patients aged 6 - 35 months and 36 - 59 months. The VE of partial vaccination and full vaccination for children aged 6 - 35 months were 21.6% (95% CI = - 65.1% - 62.7%) and 40.6% (95% CI = - 66.0% - 78.8%), respectively. ConclusionThe overall VE of influenza vaccination was 36.8% among 6 - 59 months old children, with a higher VE against SARI than that against ILI and a higher VE among the children aged 36 - 59 months than that among those aged 6 - 35 months. Full dose influenza vaccination provided better protection than partial dose vaccination for children aged 6 - 35 months.